2013
DOI: 10.1007/s10753-013-9675-2
|View full text |Cite
|
Sign up to set email alerts
|

As a New Inflammatory Marker for Familial Mediterranean Fever: Neutrophil-to-Lymphocyte Ratio

Abstract: Familial Mediterranean fever (FMF), which is an autosomal recessive disease, is characterised by recurrent febrile episodes in association with peritonitis, pleuritis and arthritis and has ongoing subclinical inflammation during attack-free period. In this study, we aimed to investigate the relationship between FMF with neutrophil-to-lymphocyte ratio (NLR), which is determined in many chronic inflammations as a new potential inflammatory mediator. We included 62 patients and 41 healthy subjects who were simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 42 publications
7
106
0
10
Order By: Relevance
“…Ahsen and co-workers were sad; NLR might be used in the Familial Mediterranean Fever patient as an indicator of the subclinical inflammation [9]. Gunay and colleagues found an doi: 10.5455/medscience.2015.04.8265…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahsen and co-workers were sad; NLR might be used in the Familial Mediterranean Fever patient as an indicator of the subclinical inflammation [9]. Gunay and colleagues found an doi: 10.5455/medscience.2015.04.8265…”
Section: Discussionmentioning
confidence: 99%
“…This marker is cheap, readily accessible and can be calculated quite easily. Recently, neutrophil/lymphocyte ratio (NLR) has been shown to reflect inflammatory burden in some acute inflammatory diseases like to AA [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Makay et al (20) reported that there was no significant difference in MPV levels between FMF patients during attack-free period and healthy controls, while significant reduction in MPV levels were detected during attacks in comparison to attack-free period. In addition, free from attack status, Abanonu et al found no significant difference in MPV levels between FMF patients and healthy controls (21).…”
Section: Discussionmentioning
confidence: 96%
“…4,[6][7][8] On the other hand, NLR has been proposed to be a marker to evaluate systemic inflammatory condition in various chronic inflammatory diseases. [10][11][12][13][14][15][16][17] However, the relationship between disease activity in AS and NLR has not been fully demonstrated yet. NLR is also an objective measurement and does not lead to any additional cost to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 Leukocyte count and its subtypes are also well-known inflammatory markers in several diseases. 10,11 Recently, neutrophil-lymphocyte ratio (NLR) has been calculated to evaluate inflammation in various chronic inflammatory diseases such as coronary chronic total occlusion, 10 psoriasis, 11 chronic kidney disease, 12 ulcerative colitis, 13 gastric cancer, 14 chronic obstructive pulmonary disease, 15 familial Mediterranean fever, 16 and AS. 17 In addition, mean platelet volume (MPV) was reported to have a predictive value of inflammation in chronic obstructive pulmonary disease, 15 inflammatory bowel disease, 18 rheumatoid arthritis (RA) and AS.…”
mentioning
confidence: 99%